A molecular assay for sensitive detection of pathogen-specific T-cells. - Victoria O Kasprowicz; Jessica E Mitchell; Shivan Chetty; Pamla Govender; Kuan-Hsiang Gary Huang; Helen A Fletcher; Daniel P Webster; Sebastian Brown; Anne Kasmar; Kerry Millington; Cheryl L Day; Nompumelelo Mkhwanazi; et al. (PLoS ONE)
Here we describe the development and validation of a highly sensitive assay of antigen-specific IFN-γ production using real time quantitative PCR (qPCR) for two reporters--monokine-induced by IFN-γ (MIG) and the IFN-γ inducible protein-10 (IP10). We developed and validated the assay and applied it to the detection of CMV, HIV and Mycobacterium tuberculosis (MTB) specific responses, in a cohort of HIV co-infected patients. We compared the sensitivity of this assay to that of the ex vivo RD1 (ESAT-6 and CFP-10)-specific IFN-γ Elispot assay. We observed a clear quantitative correlation between the two assays (P<0.001). Our assay proved to be a sensitive assay for the detection of MTB-specific T cells, could be performed on whole blood samples of fingerprick (50 uL) volumes, and was not affected by HIV-mediated immunosuppression. This assay platform is potentially of utility in diagnosis of infection in this and other clinical settings.